The Effect of Skintific Product Endorser Competence On Tiktok Social Media Towards Purchasing Decisions for Skincare Products UNJ Communication Science Students - Huwwaida, Nabillah (Universitas Sang Bumi Ruwa Jurai, 2025)
Media plays an important role in conveying information and influencing people's behavior, especially in the context of business and politics. With technological advances, social media such as TikTok has become a significant platform for product promotion, including in the beauty sector. This study aims to analyze the effect of Skintific product endorser competence on TikTok on purchasing decisions for skincare products among Communication Science students at Universitas Negeri Jakarta (UNJ). Through a quantitative approach, this study uses a purposive sampling method with 30 respondents who actively use TikTok and are exposed to Skintific product promotional content. The main focus of the research is to identify how much influence endorser competence has on purchasing decisions and the factors that are most influential in the process. The results are expected to provide insight into the effectiveness of endorsements on social media and their contribution to consumer behavior. Using statistical analysis, this study will test the proposed hypothesis, namely whether there is a significant effect of endorser competence on purchasing decisions. The findings of this study are expected to contribute to marketing strategies in the digital era as well as enrich the literature on the role of social media in consumer decision making.